2020
DOI: 10.1128/msphere.00760-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluations of the Pathogenesis of Candida auris Phenotypes and Candida albicans Using Clinically Relevant Murine Models of Infections

Abstract: The newly emerged Candida species Candida auris is associated with an exponential rise in life-threatening invasive disease in health care facilities worldwide. Unlike other species, C. auris exhibits a high level of transmissibility, multidrug resistance, and persistence in the environment, yet little is known about its pathogenesis largely due to limited data from animal models. Based on in vitro biofilm evaluations and confocal laser scanning microscopy, C. auris phenotypes with different biofilm-forming ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 56 publications
0
30
0
2
Order By: Relevance
“…Therefore, to substantiate our in vitro findings on enhanced S. aureus antimicrobial tolerance in mixed biofilms with C. albicans ( Figure 2 ), we modified the established mouse subcutaneous catheter model, which proved to be suitable for sustaining polymicrobial biofilm formation, as demonstrated by SEM analysis of explanted catheters ( Fig. 2 , 3) [ 45 , 50 ]. Vancomycin therapy was implemented at clinically relevant therapeutic doses over a period of five days in mice with single-species or mixed-species infected catheters.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, to substantiate our in vitro findings on enhanced S. aureus antimicrobial tolerance in mixed biofilms with C. albicans ( Figure 2 ), we modified the established mouse subcutaneous catheter model, which proved to be suitable for sustaining polymicrobial biofilm formation, as demonstrated by SEM analysis of explanted catheters ( Fig. 2 , 3) [ 45 , 50 ]. Vancomycin therapy was implemented at clinically relevant therapeutic doses over a period of five days in mice with single-species or mixed-species infected catheters.…”
Section: Discussionmentioning
confidence: 84%
“…infections and anti-biofilm strategies [45,50], one disadvantage is lack of blood flow, which can result in inefficient drug delivery to the biofilm within the catheter. In fact, an initial pilot study indicated no effect for vancomycin on S. aureus recovery from single-species biofilms, supporting this concern (data not shown), and therefore, to circumvent this problem, for the therapy experiments, the catheters were cut longitudinally prior to inoculation and implantation in the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este patógeno também foi encontrado fora do ambiente hospitalar devido ao fato de conseguir sobreviver por mais tempo fora do corpo humano e em temperaturas mais altas quando comparada com outras espécies de Candida. Outros fatores que colaboram com sua disseminação foram a difícil identificação laboratorial desta espécie, sendo ela confundida algumas vezes com outros tipos de Candida, bem como sua resistência medicamentosa, levando a ineficácia do tratamento (WALL et al, 2019).…”
Section: Introductionunclassified
“…albicans tem sido descrita como a espécie mais prevalente em infecções, no entanto, outras espécies de Candida por mecanismos patológicos e epidemiológicos também se destacam pela patogenicidade e apresentam uma resistência emergente a agentes antifúngicos como C. tropicalis, C. parapsilosis e C. guilliermondii (Cordeiro et al, 2013;Brilhante et al, 2014). Outra preocupação é o surgimento de novas espécies como por exemplo C. auris descoberta em 2009 e que se apresenta com distribuição cosmopolita, associada a quadro de doença invasiva com alta mortalidade devido a um alto nível de transmissibilidade, resistência a múltiplas drogas e persistência no ambiente (Vila et al, 2020;Chakrabarti & Singh, 2020).…”
Section: Introductionunclassified